Tertulian’s montanism and the montanism in the view of Eusebius of Caesarea, Cyril of Jerusalem and Epiphanius of Salamis - examination of disparities - Domagała, Marcin (Filozofia Chrześcijańska, 2023)
Tertullian is an author widely recognized as a Montanist. However, Montanism is a religious movement that has been strongly condemned by Christian thinkers. The main purpose of the article is to explain why it is incorrect to consider Tertullian as a representative of the such form of Montanism that was transmitted to us by Eusebius of Caesarea, Cyril of Jerusalem and Epiphanius of Salamis.